Comparison of Lipid Profile Among the Different Stages of Chronic Kidney Disease in Children (KYAMC Journal, 2019)
Background: Chronic Kidney Disease (CKD) is associated with significantly increased morbidity and mortality. Children with (CKD)/End stage renal disease (ESRD) exhibit various co-morbidities, including dyslipidemia. Hypertriglyceridemia is inversely correlated with renal function. Children with advanced chronic kidney disease or end stage renal disease developed atherosclerosis and cardiovascular disease. Objectives: To measure the lipid profile in kidney disease and comparison of lipid profile among the different stages of CKD.Materials and Methods: A cross sectional analytic study to measure and compare lipid profile in fifty children with different stages of chronic kidney disease during January 2016 to June 2016 by purposive sampling technique and divided into two groups, Children with CKD stage iii and iv included in Group I and CKD stage V and V(D) included in Group II.Results: Out of Fifty children with CKD, 28(56%) were male and 22 (44%) male, 30(60%) were of11-15 year age group and 32(64%) were from rural area and 18(36%) from urban area. The etiology of CKD in two groups glomerulonephritis were 14(28%), obstructive uropathy 15 (30%), hypoplasia/dysplasia 9(18%), polycystic kidney disease 9(18%) and acute kidney injury 3(6%). All the cases were anemic, 26(52%) were hypertensive and 20(40%) had osteodystrophy.Conclusion: Dyslipidemia specially hypertriglyceridemia is common in children with CKD. Hypertriglyceridemia is inversely related to severity of CKD stages.KYAMC Journal Vol. 10, No.-3, October 2019, Page 137-142